2019
DOI: 10.2147/ijnrd.s216673
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Importance of Tubular Function in Chronic Kidney Disease</p>

Abstract: Glomerular filtration rate (GFR) and proteinuria-albuminuria are the renal functional parameters currently used to evaluate chronic kidney disease (CKD) severity. However, tubular secretion is another important renal functional parameter to be taken into account since proximal tubule (PT) secretion, in particular, is a crucial renal mechanism for endogenous organic cations, anions and drug elimination. The residual diuresis is a relevant survival predictor in patients on dialysis, since their urine is produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Consequently, glycan alterations are found in many diseases, including hereditary disorders, immune deficiencies, cardiovascular disease, and cancer [63][64][65][66][67][68][69][70][71][72]. In addition, multiple studies have identified mutations in the BBM glycoproteins megalin and cubilin that are associated with kidney disease often manifested by proteinuria [73][74][75][76][77][78][79][80][81][82]. Further, ligand binding of both these multiligand receptors is impacted by their glycan state which would have a direct impact on levels of proteinuria [83][84][85][86].…”
Section: Comparison Between Proteinuria and Hypertension Groups And Control Groupmentioning
confidence: 99%
“…Consequently, glycan alterations are found in many diseases, including hereditary disorders, immune deficiencies, cardiovascular disease, and cancer [63][64][65][66][67][68][69][70][71][72]. In addition, multiple studies have identified mutations in the BBM glycoproteins megalin and cubilin that are associated with kidney disease often manifested by proteinuria [73][74][75][76][77][78][79][80][81][82]. Further, ligand binding of both these multiligand receptors is impacted by their glycan state which would have a direct impact on levels of proteinuria [83][84][85][86].…”
Section: Comparison Between Proteinuria and Hypertension Groups And Control Groupmentioning
confidence: 99%
“…As well as their role in homeostasis described above, SLCs and ABCs transporters are also involved in detoxification processes by contributing to the renal handling of metabolic wastes, environmental chemicals and uremic toxins [ 27 ]. Uremic toxins are compounds normally eliminated by the kidney, which accumulate in the case of chronic kidney disease, causing several complications, including nephropathy [ 11 ]. The list of these molecules is available on the network of the European Uremic Toxin Workgroup ( ).…”
Section: Role Of Tubular Transporters In Maintaining Renal Cells’ mentioning
confidence: 99%
“…These substrates comprise electrolytes (e.g., Na + , Cl − , K + , Ca 2+ ), glucose, amino acids, several important anions (e.g., phosphate and citrate), uremic toxins (e.g., p-cresol, indoxyl sulfate, hippuric acid) as well as xenobiotics, some of which are used during the post-transplantation period (e.g., immunosuppressants, antibiotics, antiviral drugs). Owing to the bi-directional exchange they allow, proximal tubular cells are involved in renal and whole-body homeostasis, detoxification processes and xenobiotic clearance [9][10][11]. The effects of IR on the metabolism and structure of proximal tubular cells have been widely studied [12,13], but its effects on expression and activity of membrane transporters is less known and has not been reviewed so far.…”
Section: Introductionmentioning
confidence: 99%
“…Originally known as the New Kidney Transporter (NKT), hOAT1 is a multi-specific transporter mostly expressed in kidneys [15,16], at the basolateral membrane of proximal tubular cells (PTC) where it participates in the substrate uptake phase of blood-urine PTC exchanges [17,18]. hOAT1 transports mostly anionic compounds, including xenobiotics such as antiviral acyclic nucleoside phosphonates (e.g., tenofovir, adefovir) [19], endogenous compounds and metabolites (e.g., mono-and di-carboxylates) including uremic toxins, especially protein-bound uremic toxins (e.g., indoxyl sulfate, p-cresol sulfate) [8,9,20,21]. Therefore, hOAT1 dysfunctions are not only associated with the impairment of xenobiotic elimination, but also with pathophysiological conditions owing to increased systemic retention of uremic toxin such as in Chronic Kidney Disease [8,9,21].…”
Section: Introductionmentioning
confidence: 99%
“…From the physiological point of view, MFS transporters also play an essential role in maintaining homeostasis at the systemic and cellular scales. MFS transporters are involved in cellular nutrient disposition [2,3] (e.g., sugar porters including Glucose transporters -GLUTsfamily) as well as in detoxification processes [5,8,9] (e.g., Organic Anion Transporter family). By modulating body fluid and tissue concentrations of a broad range of specific endo/exogenous molecules, MFS transporters might even drive hormone-independent remote inter-organ communications [10].…”
Section: Introductionmentioning
confidence: 99%